Ain Shams University- Paving the way towards a paperless University - Sherien Elagroudy; Wesam M Elbardisy; Ghada F Hassan; Abdelfattah Saoud; Mahmoud A.S. El-Meteini (Journal of Sustainability Perspectives, 2023)
The conventional use of paper-based operations in daily working practices introduces numerous risks and financial burdens. Nowadays, Universities are aligning with the growing movement of "green" campuses. Going paperless is a green initiative contributing to sustainable development goals 11 and 12. Ain Shams University (ASU) attempted to establish a paperless campus through digital transformation as this movement promises high-quality academic and administrative services. This paper aims to highlight ASUs developed 3 R’s approach for paper waste reduction include switching to electronic exams, customizing paper amounts annually, implementing electronic payment and service options, and using barcodes for cafeterias by creating E-Systems to deliver services online. Starting with the ASU community’s cultural level, awareness campaigns are being conducted on proper waste management. Parallelly, segregation bins are placed throughout the campus to effectively separate waste streams for recycling options, either internally by the artistic activities or externally by our specialized partners. To ensure the efficiency of this digital transformation, this study investigates the different waste streams, generation rates and quantities. Statistical methods will be used to analyze relationships between variables and identify potential paper waste reduction and recycling plans. The outcome of this study is an evaluation of the current progress in implementing the strategy. Additionally, it could be used as a case study for developing strategies in moving toward establishing a successful paperless university model